Infographics on signs and symptoms of metastatic (secondary) breast cancer can empower women with a breast cancer diagnosis - Derakshan, Nazanin; Taylor, Joanne; Chapman, Bethany (Frontiers in Psychology, 2024)
We investigated the usefulness of a metastatic (secondary) breast cancer Infographics designed to enhance knowledge about symptoms of metastatic breast cancer in women diagnosed with breast cancer. Women with a primary or metastatic diagnosis of breast cancer who had not been in receipt of the Infographics previously, were sent the Infographics and asked to complete a questionnaire measuring their views of the usefulness of the Infographics in a number of domains. They were also asked to complete questionnaires on anxiety and depression, coping, emotion regulation strategies and perceived cognitive functioning. Results showed that women advocated the use of the Infographics in medical and health care settings, as well as its ability in equipping them with the relevant knowledge on signs of recurrence, its benefits in empowering control and reducing fears and uncertainties regarding metastatic breast cancer. Exploratory analysis showed that individual differences in trait vulnerability to anxiety and in emotion regulation strategies modulated women’s responses suggesting the use of tailored approaches in the communication of the Infographics with patients. . Our results point to the overall benefits of the Infographics in a number of domains. . Implications for applications in healthcare settings are discussed.